Caracterización morfológica de hongos endófitos asociados a cacao nativo y su capacidad antagónica para el control de Moniliophthora Perniciosa - Rodríguez del Castillo, Ginsberg (2011)
This research was conducted with the objective of characterizing morphologically the endophytic fungi associated with native cocoa to assess their antagonistic ability to control Moniliophthora perniciosa. It was developed in the laboratory of Plant Pathology of Instituto de Cultivos Tropicales(ICT), located in the district of Banda Shilicayo, province and department of San Martin. For the morphological characterization was used 68 isolates of endophytic fungi from Alto Amazonas. Variables and categories were employed to determine the genetic distance with 185 markers, which was calculated using the DICE coefficient (Dice, 1945). Cluster analysis was done using the algorithm UPGMA (Unweighted Pair-Group Method Arithmetic Average usingn) using the Darwin program (Dissimilarity Analysis and Representation for Windows). To evaluate the antagonistic capacity of fungal endophytes, were carried out test for antibiosis and mycoparasitism through the production of soluble inhibitory metabolites and method of precolonizada plate respectively, for both tests was used the Completely Randomized Design (CRD). The cluster analysis was able to form eight big groups A, B, C, D, E, F, G and H corresponding to the genera of Trichoderma (T-E), Clonostachys (Cl-E), Botryosphaeria (Bo-E ) Xylaria (X-E), Pestalotiopsis (P-E), Acremonium (Acr-E), Fusarium (F-E) and Colletotrichum (Coll-E), respectively, and these at the same time are subdivided into 20 morphotypes (A1, A2, A3 , A4, B1, B2, B3, C1, C2, C3, D1, E1, F1, G1, G2, G3, G4, H1, H2 and H3). Likewise, the analysis of dispersion, was able to form four groups far between. The Trichoderma and Clonostachys genera showed a close approach; between Colletotrichum and Fusarium, and Botryosphaeria, Pestalotiopsis, Xylaria showed a slightly approach . However, the Acremonium genus was the most distant of the other genera. The isolation TE-17 proved to be a potential biocontrol in vitro, was able to inhibit (100%) the mycelial growth of M. perniciosa, followed by isolation Bo-E-107 that inhibited 45.2% compared of isolates Cl-E-61, Cl-E-119 and Coll-E-33 that had no effect on mycelial inhibition. Likewise, TE-17 proved to be the only aggressive mycoparasite (100% colonization), compared to other isolates of endophyte fungi that had no effect on mycoparasitism of M. perniciosa.